The SOD Mimic, MnTE-2-PyP, Protects from Chronic Fibrosis and Inflammation in Irradiated Normal Pelvic Tissues - Shashank Shrishrimal (Antioxidants, 2017)
Pelvic radiation for cancer therapy can damage a variety of normal tissues. In this study, we demonstrate that radiation causes acute changes to pelvic fibroblasts such as the transformation to myofibroblasts and the induction of senescence, which persist months after radiation. The addition of the manganese porphyrin, MnTE-2-PyP, resulted in protection of these acute changes in fibroblasts and this protection persisted months following radiation exposure. Specifically, at two months post-radiation, MnTE-2-PyP inhibited the number of α-smooth muscle actin positive fibroblasts induced by radiation and at six months post-radiation, MnTE-2-PyP significantly reduced collagen deposition (fibrosis) in the skin and bladder tissues of irradiated mice. Radiation also resulted in changes to T cells. At two months post-radiation, there was a reduction of Th1-producing splenocytes, which resulted in reduced Th1:Th2 ratios. MnTE-2-PyP maintained Th1:Th2 ratios similar to unirradiated mice. At six months post-radiation, increased T cells were observed in the adipose tissues. MnTE-2-PyP treatment inhibited this increase. Thus, MnTE-2-PyP treatment maintains normal fibroblast function and T cell immunity months after radiation exposure. We believe that one of the reasons MnTE-2-PyP is a potent radioprotector is due to its protection of multiple cell types from radiation damage.